Restorative justice and victims: Not a self-evident relationship - Pemberton Antony; Winkel Frans W.; Groenhuijsen Mark (Temida)
The two most prominent developments in criminal justice in the last twenty to thirty years are the rise of restorative justice and the recognition and improvement of the position of the victim. The first part of the paper discusses a theoretical model for victims within restorative justice that the researchers at the InterVICT research institute authors of this paper) are developing at this moment. This model incorporates current knowledge from social psychology and studies surrounding traumatic stress and provides a number of hypotheses that will be subsequently evaluated in practice with participants in restorative justice procedures. On the other hand, international legal protocols for restorative justice also lack a consistent victim-oriented perspective. To this end the European Forum for Victim Services has recently published a statement concerning the position of the victim within mediation. The second part of the paper addresses the central issues in this statement. Taken together the paper moves beyond criticism of restorative justice, as it hopes to redirect theory and implementation of restorative justice toward a stronger victim-orientation.